1994
DOI: 10.1021/jf00041a013
|View full text |Cite
|
Sign up to set email alerts
|

Ailanthus excelsa Roxb. (SIMAROUBACAE), a Promising Source of Leaf Protein

Abstract: Fresh leaves of Ailanthus excelsa and three protein fractions, unfractionated, chloroplastic, and cytoplasmic, as well as pressed cake left after extraction of protein were subjected to proximate analysis. The cytoplasmic protein fraction contained 62.71 % crude protein, while whole leaf contained 20.86%. The unfractionated and chloroplastic protein fractions contained more crude fat than the whole leaf and pressed cake. Compared to whole leaf and pressed cake, protein fractions were low in crude fiber. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…celsa have demonstrated the presence of quassinoids, fl avonoids, alkaloids, terpenoids, and proteins (Ogura et al, 1977;Loizzo et al, 2007;Joshi et al, 2003a;Sherman et al, 1980;Nag and Matai, 1994). A. excelsa extracts and some of its isolated compounds have demonstrated medicinal properties such as signifi cant antileukemic, antibacterial, antifungal, and antifertility activities (Ogura et al, 1977;Dhanasekaran et al, 1993;Shrimali et al, 2001;Joshi et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…celsa have demonstrated the presence of quassinoids, fl avonoids, alkaloids, terpenoids, and proteins (Ogura et al, 1977;Loizzo et al, 2007;Joshi et al, 2003a;Sherman et al, 1980;Nag and Matai, 1994). A. excelsa extracts and some of its isolated compounds have demonstrated medicinal properties such as signifi cant antileukemic, antibacterial, antifungal, and antifertility activities (Ogura et al, 1977;Dhanasekaran et al, 1993;Shrimali et al, 2001;Joshi et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…It catalyses the conversion of angiotensin I into the active vasoconstrictor octapeptide, angiotensin II (Brown and Hall, 2005). Angiotensin converting enzyme (ACE) inhibitors are widely used for the treatment of cardiovascular disease since they improve blood pressure, control patients with hypertension and prolong survival in patients with acute myocardial infarction (Shlipak et al, 2001), asymptomatic left ventricular dysfunction (Borghi et al, 2005), congestive heart failure (Carson, 2000) and renal dys-Previous phytochemical studies on A. excelsa have demonstrated the presence of quassinoids, alkaloid, terpenoids and proteins (Ogura et al, 1977;Joshi et al, 2003a;Sherman et al, 1980;Nag and Matai, 1994). A. excelsa extracts and some isolated compounds have demonstrated medicinal properties such as significant antileukemic, antibacterial, antifungal and antifertility activities (Ogura et al, 1977;Dhanasekaran et al, 1993;Shrimali et al, 2001;Joshi et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Some bioactive constituents have also been found in the bark, leaves, roots, etc., of this plant, which have significant antibacterial, antifungal and antifertility activities [6][7][8]. It has been reported that leaves of this plant are a good source of digestible leaf proteins and calcium [9,10]. However, seeds of A. excelsa are still not used and are considered a nontraditional source.…”
Section: Introductionmentioning
confidence: 99%